Chamber housing a sculpture of the goddess Adi Shakti - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha, or inner sanctum, of the temple, is a small and dimly lit chamber currently housing a sculpture of the Goddess Adi Shakti. The only decoration visible is at the entrance of this space: the T-shaped doorframe which has multiple decorated shakhas (vertical mouldings on the door jamb). The bottom of the shakha depicts the river Goddess Ganga and Yamuna which are presently in a bad state of preservation.